Clima organizacional en los trabajadores de la Corporación Nacional de Telecomunicaciones CNT EP Chimborazo año 2024. - Barreno Torres, Daniel Alexander (2025)
In the Ecuadorian context, public institutions should implement organizational climate assessment mechanisms. The National Telecommunications Corporation (CNT EP) actively participated in these assessments between 2020 and 2023, with results ranging from 76% to 82%. While these scores were classified as "Very Good," critical areas were identified that motivated the development of this research. For the study, the structured survey method was chosen, one of the various existing methodologies for analyzing organizational climate and job satisfaction, using a Likert scale adapted from a previous study and validated through a pilot test with Cronbach's Alpha and KMO. The questionnaire was distributed online, with institutional support, and was aimed at permanent employees. The data were analyzed using SPSS version 23. The results showed a significant relationship between both variables using the chi-square test (p > 0.05) and Cramer's V coefficient (0.370), which guarantees a strong relationship between them. A positive psychology manual is proposed with practical strategies to strengthen emotional well-being, coexistence, and staff commitment.